Personal and social facilitators of student engagement: transition into higher education - Vardal-Ocakli, Sermin; Ok, Ahmet (Frontiers in Education, 2024)
Facilitating student engagement at all levels of higher education is critical, but since transition-year experiences pave the way for further engagement, it requires more attention.Considering its significance and impact on students' life-changing decisions and attitudes, this study was designed with a major focus on the personal and social facilitators of engagement and was conducted with 165 university students, who were both language learners and the transition-year students. In line with the theoretical model of Skinner and Pitzer (2012), how well personal facilitators would predict the performance of transition-year students and what expectations these students held concerning social facilitators were questioned. The former investigation required the correlational method, whereas the descriptive survey method was preferred for the latter one. The results of both the hierarchical regression and descriptive analyses indicated that both personal (self-efficacy, sense of belonging, language strategy use) and social facilitators (need-supportive teacher practices and school activities) are essential for transitional year student engagement.